Ge doping of GaN beyond the Mott transition. (5th October 2016) - Ajay, A; Schörmann, J; Jiménez-Rodriguez, M; Lim, C B; Walther, F; Rohnke, M; Mouton, I; Amichi, L; Bougerol, C; Den Hertog, M I; Eickhoff, M; Monroy, E
Abstract: We present a study of germanium as n-type dopant in wurtzite GaN films grown by plasma-assisted molecular-beam epitaxy, reaching carrier concentrations of up to 6.7  ×  10 20 cm −3 at 300 K, well beyond the Mott density. The Ge concentration and free carrier density were found to scale linearly with the Ge flux in the studied range. All the GaN:Ge layers present smooth surface morphology with atomic terraces, without trace of pits or cracks, and the mosaicity of the samples has no noticeable dependence on the Ge concentration. The variation of the GaN:Ge band gap with the carrier concentration is consistent with theoretical calculations of the band gap renormalization due to electron–electron and electron–ion interaction, and Burstein–Moss effect.